Correlation of serum homocysteine levels in pregnancy related hypertensive disorders versus normotensive pregnancies - Hymavathi, Kalki; Shukla, Neha; Madhuri, P.V. Sreeleena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Homocysteine concentrations decrease during normal pregnancy, but this does not occur in pre-eclampsia. In pre-eclampsia, homocysteine levels further increase with severity of pre-eclampsia. Elevated homocysteine levels can be due to genetic or multifactorial deficit or a combination of both. Methods: The present study is conducted at department of obstetrics and gynaecology, Narayana Medical College and Hospital, Nellore. 200 pregnant (100 women with pregnancy related hypertensive disorders and 100 normotensive pregnants) recruited. Maternal serum Homocysteine levels were analyzed among women with pregnancy related hypertensive disorders and compared with normotensive pregnant. Chemiluminescence immunoassay was used for determining the Homocysteine levels. Results: The study revealed significant elevation in the levels of homocysteine in pre-eclamptic women (17.54±5.34) compared to normotensive women (7.59±1.91). The study showed a strong association between serum homocysteine levels and severity of pre-eclampsia. The mean homocysteine levels in women with severe Pre-eclampsia (20.59±4.3) were significantly higher than those with mild pre-eclampsia (15.17±1.9). A positive correlation is found between homocysteine levels with serum uric acid and LDH demonstrating the harmful action of hyperhomocysteinemia upon the endothelium. A negative correlation is found between homocysteine levels with hemoglobin and hematocrit even though in anemic patients the hematological levels are found to be little high due to hemoconcentration. The perinatal outcome in women with raised levels of homocysteine was poor with an increased incidence of IUGR (41%), SGA (9%), still births (3%) and IUD (4%) among women with pregnancy related hypertensive disorders when compared to normotensive pregnant women. Conclusions: Elevated levels of homocysteine can be reduced by administering vitamins which help by increasing the metabolism of homocysteine. The internationally accepted treatment for hyperhomocystenemia is using a combination of folic acid 400 µg, vitamin B12 500 µg and pyridoxine 10mg initiating from pre-conceptional period can be used.